Sustainable supply chain management: current debate and future directions - Bruno Silvestre (Gestão & Produção)
Abstract This paper is a research brief on sustainable supply chain management and covers some of the key elements of literature’s past debate and trends for future directions. It highlights the growth of this research area and reinforces the importance of a full consideration of all three key dimensions of sustainability when managing sustainable supply chains, i.e., the financial, environmental and social dimensions. Therefore, supply chain decision makers need to unequivocally assess the impact of their decisions on the financial, environmental and social performances of their supply chains. This paper also argues that risks and opportunities are the key drivers for supply chain decision makers to adopt sustainability within their operations, and that barriers to sustainability adoption exist. This research highlights that, depending on the focus adopted, supply chains can evolve and shift from more traditional to more sustainable approaches over time. The paper concludes with some promising avenues for future investigation.